"Clocks Must Always Be Turned Back": Brown v. Board of Education and the Racial Origins of Constitutional Originalism. Issue 3 (16th August 2021) - TERBEEK, CALVIN
Abstract : The Republican Party has adopted constitutional "originalism" as its touchstone. Existing accounts of this development tell either a teleological story, with legal academics as the progenitors, or deracialized accounts of conservatives arguing first principles. Exploiting untapped archival data, this paper argues otherwise. Empirically, the paper shows that the realigning GOP's originalism grew directly out of political resistance to Brown v. Board of Education by conservative governing elites, intellectuals, and activists in the 1950s and 1960s. Building on this updated empirical understanding, the theoretical claim is that ideologically charged elite legal academics and attorneys in Departments of Justice serve more of a legitimating rather than an originating role for American constitutional politics upon a long coalition's electoral success. Finally, by showing the importance of race to constitutional conservatism's development, this article posits that the received understanding of a "three-corner stool" of social, economic, and foreign policy conservatism needs revision.